Analysis of Nonlinear Characteristic and Performance Continuity Reliability of Rolling Bearing Vibration - Cheng Li; Xia Xintao; Ye Liang (Jixie chuandong)
In order to analyze the relationship between the nonlinear characteristics and the performance continuity reliability of rolling bearing vibration, based on chaos theory, a new concept is proposed for continuity relation dimension to characterize the nonlinear characteristics of rolling bearing vibration. Simultaneously， based on the maximum entropy principle and Poisson counting principle, the vibration performance continuity reliability model of the rolling bearing is established, and then the matching sequence of nonlinear characteristics and the vibration performance continuity reliability of the rolling bearing vibration are established. The experimental results show that the evolution of nonlinear characteristics and the vibration performance continuity reliability of rolling bearing vibration are closely related to each other, and the trend of change is consistent and reliability changes can be inferred based on the changing trend of the relation dimension. The proposed method provides a novel idea for the reliability prediction of rolling bearings.